Application Of Genetic Algorithms In Optical CDMA Communications - Ho , Chin Kuan (2002)
Genetic algorithm (GA) and its hybrid version have been investigated for designing optical orthogonal codes (OOCs) used in optical code division multiple access ( optical CDMA) networks. Results obtained by GAs and its modified version are compared with other design methods based on Galois fields. It is observed that GAs yield improved performance over the other methods and will be applicable to other kinds of spreading code design.